Measurement of the time-dependent CP asymmetry in B0 → J/ψ K0S decays - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
This Letter reports a measurement of the CP violation observables S J/ψK0S and C J/ψK0S in the decay channel B0 → J/ψ K0S performed with 1.0 fb-1 of pp collisions at √s = 7 TeV collected by the LHCb experiment. The fit to the data yields S J/ψ K0 S = 0.73 ± 0.07 (stat) ± 0.04 (syst) and C J/ψK0S = 0.03 ± 0.09 (stat) ± 0.01 (syst). Both values are consistent with the current world averages and within expectations from the Standard Model. © 2013 CERN.